High field plasmonics and laser-plasma acceleration in solid targets. (20th October 2015) - Sgattoni, A; Fedeli, L; Cantono, G; Ceccotti, T; Macchi, A
Abstract: The interaction of low intensity laser pulses with metal nano-structures is at the basis of plasmonics and the excitation of surface plasmon polaritons (SP) is one of its building blocks. Some of the configurations adopted in classical plasmonics can be explored considering high intensity lasers interacting with properly structured targets. SP excitation at intensities such that the electrons quiver at relativistic velocities, poses new questions and might open new frontiers for manipulation and amplification of high power laser pulses. Here we discuss two configurations which show evidence of the resonant coupling between relativistically intense laser pulses with the SPs on plasma targets with surface modulations. Evidences of SP excitation were observed in a recent experiment when a high contrast (10 12 ), high intensity laser pulse ( W cm −2 ) was focussed on a grating target (engraved surface at sub-micron scale); a strong emission of multi-MeV electron bunches accelerated by SPs was observed only in conditions for the resonant SP excitation. Theoretical and numerical analysis of the Light-Sail (LS) Radiation Pressure Acceleration (RPA) regime show how the plasmonic resonant coupling of the laser light with the target rippling, affects the growth of Rayleigh Taylor Instability (RTI) driven by the radiation pressure.